Effect of flow velocity and temperature on ignition characteristics in laser ignition of natural gas and air mixtures. (March 2015) - Griffiths, J.; Riley, M.J.W.; Borman, A.; Dowding, C.; Kirk, A.; Bickerton, R.
Abstract: Laser induced spark ignition offers the potential for greater reliability and consistency in ignition of lean air/fuel mixtures. This increased reliability is essential for the application of gas turbines as primary or secondary reserve energy sources in smart grid systems, enabling the integration of renewable energy sources whose output is prone to fluctuation over time. This work details a study into the effect of flow velocity and temperature on minimum ignition energies in laser-induced spark ignition in an atmospheric combustion test rig, representative of a sub 15 MW industrial gas turbine (Siemens Industrial Turbomachinery Ltd., Lincoln, UK). Determination of minimum ignition energies required for a range of temperatures and flow velocities is essential for establishing an operating window in which laser-induced spark ignition can operate under realistic, engine-like start conditions. Ignition of a natural gas and air mixture at atmospheric pressure was conducted using a laser ignition system utilizing a Q-switched Nd:YAG laser source operating at 532 nm wavelength and 4 ns pulse length. Analysis of the influence of flow velocity and temperature on ignition characteristics is presented in terms of required photon flux density, a useful parameter to consider during the development laser ignition systems. Highlights: Laser ignition of natural gas and air conducted in an atmospheric pressure combustion test rig. Minimum ignition energy for a natural gas–air mixture under engine like conditions investigated. Analysis of influence of flow velocity and temperature on ignition characteristics conducted. Required threshold photon flux density for ignition of a natural gas–air mixture determined.